Notes on Docosia Winnertz (Diptera: Mycetophilidae), with description of six new species from Central Asia and the first generic record from the Afrotropical region - Kurina, Olavi; Ševčík, Jan (Zootaxa, 2012)
Six new species of Docosia Winnertz are described from Central Asia and their terminalia illustrated, viz. Docosia bartaki sp. nov. (Uzbekistan), D. blagoderovi sp. nov. (Uzbekistan), D. chimganica sp. nov. (Uzbekistan), D. distributa sp. nov. (Turkmenistan, Kazakhstan), D. koyentagi sp. nov. (Turkmenistan) and D. turkmenica sp. nov. (Turkmenistan). A new record of D. selini Kurina from Uzbekistan and a key to Docosia species in Central Asia are provided. The number of Docosia species in Central Asia now totals 10. Docosia gilvipes (Haliday in Walker) is newly found in South Africa representing the first record of the genus from the Afrotropical region.